2013
DOI: 10.1093/infdis/jit241
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Pathogen-Specific T-Helper 1 and T-Helper 17 Cells in Pulmonary Tuberculosis With Coincident Type 2 Diabetes Mellitus

Abstract: Therefore, our data reveal that tuberculosis in persons with DM is characterized by elevated frequencies of Th1 and Th17 cells, indicating that DM is associated with an alteration in the immune response to tuberculosis, leading to a biased induction of Th1- and Th17-mediated cellular responses and likely contributing to increased immune pathology in M. tuberculosis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
101
4
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 33 publications
8
101
4
7
Order By: Relevance
“…Indeed, it has been previously demonstrated that CD4 1 T cells producing IL-17A and IFN-g are increased in frequency and magnitude and promote inflammation and that several cytokines produced by Th1 or Th17 cells have been linked to insulin resistance (22)(23)(24). In addition, patients with type 2 diabetes also have been shown to exhibit decreased frequencies of natural regulatory T cells, indicating the presence of an unbalanced proinflammatory milieu in type 2 diabetes (7,24). Thus, underlying poorly controlled diabetes by itself could contribute to the increase in type 1 and 17 cytokines observed in individuals with tuberculosis and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been previously demonstrated that CD4 1 T cells producing IL-17A and IFN-g are increased in frequency and magnitude and promote inflammation and that several cytokines produced by Th1 or Th17 cells have been linked to insulin resistance (22)(23)(24). In addition, patients with type 2 diabetes also have been shown to exhibit decreased frequencies of natural regulatory T cells, indicating the presence of an unbalanced proinflammatory milieu in type 2 diabetes (7,24). Thus, underlying poorly controlled diabetes by itself could contribute to the increase in type 1 and 17 cytokines observed in individuals with tuberculosis and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Hematology was performed on all individuals, using the Ac$T 5diff hematology analyzer (Beckman Coulter, Brea, CA). This study comprised a separate set of individuals compared with our previous study on tuberculosis and diabetes (7). All individuals were examined as part of a clinical protocol approved by the Institutional Review Board of the National Institute of Research in Tuberculosis (NCT01154959), and informed written consent was obtained from all participants.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Chronic hyperglycemia may disrupt the regulation of key cytokines, such as interferon-gamma, which in turn may increase the M. tuberculosis bacterial burden and subsequent risk of death in TB-DM patients. 22 In addition, altered T-helper (Th) 1, Th 2, and Th 17 cytokine responses have been demonstrated among patients with TB-DM. 23 Diabetes mellitus (DM) is an increasingly recognized comorbidity that can both accelerate TB disease and complicate TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, altered T-helper (Th) 1, Th 2, and Th 17 cytokine responses have been demonstrated among patients with TB-DM. 23 Diabetes mellitus (DM) is an increasingly recognized comorbidity that can both accelerate TB disease and complicate TB treatment.…”
mentioning
confidence: 99%